2010
DOI: 10.1007/s12088-010-0028-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of volatile aroma constituents of wine produced from Indian mango (Mangifera indica L.) by GC-MS

Abstract: Volatile aroma compounds are synthesized by wine yeast during wine fermentation. In this study the volatile aroma composition of two varieties of mango wine were determined to differentiate and characterize the wines. The wine was produced from the fruits of two varieties of mango cultivars namely Banginapalli and Alphonso. The volatile compounds formed in mango wine were analyzed by gas chromatography coupled with mass spectrometry (GC-MS). Thirty-two volatile compounds in wines were in lower concentration. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…These figures are comparable to those in other studies on mango wine, which reported ethanol contents of between 6.5 and 10.7% (v/v) (Reddy & Reddy, 2005;Reddy et al, 2010;Pino & Queris 2011). Glycerol is a simple alcohol and a by-product formed by S. cerevisiae in order to maintain the cytosolic redox balance, especially under anaerobic conditions (Wang et al, 2001).…”
Section: Ethanol and Glycerol Contents Of Mango Winesupporting
confidence: 88%
See 3 more Smart Citations
“…These figures are comparable to those in other studies on mango wine, which reported ethanol contents of between 6.5 and 10.7% (v/v) (Reddy & Reddy, 2005;Reddy et al, 2010;Pino & Queris 2011). Glycerol is a simple alcohol and a by-product formed by S. cerevisiae in order to maintain the cytosolic redox balance, especially under anaerobic conditions (Wang et al, 2001).…”
Section: Ethanol and Glycerol Contents Of Mango Winesupporting
confidence: 88%
“…2-Phenylethyl alcohol, isoamyl alcohol and (Z)-3-hexenol were at levels higher than their threshold levels in both the non-macerated and macerated wines, and the isobutyl alcohol level was higher than its threshold in the macerated wine only (Table 2). Isoamyl alcohol is known to be a major constituent of mango wine and is responsible for the winey odour (Reddy et al, 2010). Isobutyl alcohol is responsible for the fruity and winey odours, whereas (Z)-3-hexenol can contribute an intense green grassy odour.…”
Section: Evolution Of Alcoholsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 8 Furthermore, excessive concentration of ethyl acetate generally suppresses the formation of other compounds contributing to a fruity aroma. 9 A simple and cost-effective device that can quantify the amount of ethyl acetate in wine during the wine manufacturing is of demand by wine producers since the taste of the wine will determine its grade, and subsequently the price of the wine. 10 Methods available for the analysis of air samples of ethyl acetate, such as gas chromatography and mass spectrometry, 11 are expensive and power consuming.…”
mentioning
confidence: 99%